2017
DOI: 10.3762/bjoc.13.35
|View full text |Cite
|
Sign up to set email alerts
|

(Z)-Selective Takai olefination of salicylaldehydes

Abstract: The Takai olefination (or Takai reaction) is a method for the conversion of aldehydes to vinyl iodides, and has seen widespread implementation in organic synthesis. The reaction is usually noted for its high (E)-selectivity; however, herein we report the highly (Z)-selective Takai olefination of salicylaldehyde derivatives. Systematic screening of related substrates led to the identification of key factors responsible for this surprising inversion of selectivity, and enabled the development of a modified mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is noteworthy that the opposite trans / cis selectivity was observed for ortho -disubstituted arylaldehydes, 2,6-dimethoxybenzaldehyde ( 2w ) and 2,4,6-trimethoxy-substituted ( 2x ), while keeping the high yields of the products 3w,x , suggesting that the methoxy group at the ortho -position served as a directing group to the chromium center to increase the cis -isomers. 11 In fact, these results were different from the olefination without 1a under Takai's olefination conditions: the same substrate combination of 2x and CHBr 3 in the presence of excess amounts of CrCl 2 afforded the corresponding trans -β-chloroalkene 3x′ as the major product (29%, trans : cis = 76 : 24) together with co-production of 3x in 19% yield ( trans : cis = 68 : 32) (see ESI†). In addition, the carbonyl olefination of 4,4′-diformylbiphenyl ( 2y ) gave 3y in 47% yield by increasing the reagents to the double amounts.…”
mentioning
confidence: 90%
“…It is noteworthy that the opposite trans / cis selectivity was observed for ortho -disubstituted arylaldehydes, 2,6-dimethoxybenzaldehyde ( 2w ) and 2,4,6-trimethoxy-substituted ( 2x ), while keeping the high yields of the products 3w,x , suggesting that the methoxy group at the ortho -position served as a directing group to the chromium center to increase the cis -isomers. 11 In fact, these results were different from the olefination without 1a under Takai's olefination conditions: the same substrate combination of 2x and CHBr 3 in the presence of excess amounts of CrCl 2 afforded the corresponding trans -β-chloroalkene 3x′ as the major product (29%, trans : cis = 76 : 24) together with co-production of 3x in 19% yield ( trans : cis = 68 : 32) (see ESI†). In addition, the carbonyl olefination of 4,4′-diformylbiphenyl ( 2y ) gave 3y in 47% yield by increasing the reagents to the double amounts.…”
mentioning
confidence: 90%
“…However, it has been hypothesized that the active species is either a chromium dihalido-methanide species (Scheme , A ) or more favorably the ostensible dichromium monohalido-methylidene (Scheme , B ). This uncertainty has been extensively studied over the years, substantiating species B as the likely candidate. Yet, as neither type ( A or B ) has ever been isolated, both must still be considered as the active species, especially as metal-halido-methanide complexes can initiate the olefination of aldehydes .…”
Section: Introductionmentioning
confidence: 99%
“…Based on these criteria and the dual acid–base functionality, we strategically designed and synthesized a series of new MALDI matrices I – IV (see Scheme ) containing a simple aniline derivative anchored by a carboxyl group for COOH-NH 2 ( I ) and COOH-NHMe ( IV ), and formyl group for CHO-NH 2 ( II) , and CHO-NHAc (III) . Though I – IV have been synthesized previously, their related application as a MALDI matrix as part of a rationally designed strategy have not been proposed, especially for II – IV . The amphoteric property of COOH-NH 2 ( I ) and COOH-NHMe ( IV ) could allow the detection of both positive and negative ions in MALDI. In this study, we demonstrated that these dual polarity MALDI matrix, COOH-NH 2 ( I ) and COOH-NHMe ( IV ), allowed complementary analysis of lipids and proteins, including the positively charged and negatively charged species, within one experiment.…”
mentioning
confidence: 99%